Implementasi MIRO sebagai Alat Pembelajaran Interaktif bagi Guru-Guru SMAK Thomas Aquino dengan Pendekatan Design Thinking - Helmy Syakh Alam; Anak Agung Gede Adi Mega Putra; I Komang Gede Sutrisna; I Ketut Danar Cahyadi; I Ketut Angga Saputra (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The digitalization of education has become both a challenge and an opportunity for educators to improve the quality of learning. One innovative solution that can be implemented is the use of Miro as an interactive learning tool. This community service activity aims to implement Miro as a teaching medium for teachers at SMAK Thomas Aquino using a Design Thinking approach. The methods used include interviews, observations, training sessions, and evaluations of Miro's effectiveness in classroom instruction. The main training session was held on December 20, 2024, with 19 teachers participating. The results show that most participants experienced an increased understanding of technology use in teaching and felt more confident in adopting digital-based learning methods. The success indicators of this activity include improved digital literacy among teachers, ease of using the Miro application, and increased awareness of the potential of technology as a teaching aid. One teacher stated that the application was very helpful in teaching and felt familiar due to its similarities with commonly used platforms such as Google Docs. Despite some initial challenges in logging in and adapting to the platform, the mentoring-based approach proved effective in helping teachers understand Miro’s core features. The implementation of interactive technologies like Miro can be a viable solution to enhance student engagement and learning effectiveness in the digital era.